Safety Evaluation of Aqueous Extract of Crateva adansonii Leaves on Selected Tissues of Rats (Fountain Journal of Natural and Applied Sciences, 2013)
The phytochemical constituents and safety of aqueous extract of Crateva adansonii leaves on rats were investigated. Forty rats were grouped into 4 (A-D) of 10 animals each. Group A rats received 1 mL of distilled water, while groups B, C and D received equal volume corresponding to 325, 650 and 1300 mg/kg body weight of the extract, respectively, for seven days. Five rats were sacrificed from each group 24 h after 7 doses, while the remaining five were sacrificed 24 h after discontinuing the administration for another 7 days (recovery period, day 14). Phytochemical screening revealed the presence of saponins (2.36%), alkaloids (1.34%), tannins (0.94%), phenolics (1.06%), flavonoids (0.09%), phlobatannins (0.54%) and anthraquinones (0.47%). The extract significantly increased (P0.05) with their respective controls. In contrast, the increases in the serum total protein, ALP and AST as well as decreases in liver alanine aminotransferase (ALT), serum chloride and sodium ions were sustained during the recovery period. Furthermore, the levels of serum albumin, total and conjugated bilirubin, urea, creatinine, potassium, bicarbonate, haematological parameters and computed organ-body weight ratios were not significantly (p>0.05) altered. The histology of the kidney and small intestine were preserved whereas there was mild degeneration and congestion of the hepatocytes surrounding the central veins in the liver. Overall, the extract caused mild, selective and reversible changes in the haematological profile and biochemical parameters of organ function. Therefore, because the rats recovered from the assault of the extract, the plant may still be explored as oral remedy.Keywords: Crateva adansonii; Organ dysfunction; Selective toxicity; recovery; transient effect, histoarchitecture